PERANCANGAN APLIKASI PEMANTAU PEDAGANG KELILING BERBASIS ANDROID - Dimas Ramadhan Amrulloh, - (2020)
Smartphone is an important tool for life and can be used as a source of information. One of them is an Android-based merchant monitoring application that will be applied to smartphones. The purpose of this study is to create an application that can increase the movement of traveling merchants and find out what factors influence the accuracy of GPS on smartphones in determining the position of mobile traders. The method used in the design of this application is a waterfall where research starts from analysis and needs, literature studies, application planning, model making and design, algorithm construction, testing and analysis of programs. The results of this study are traveling merchant monitoring applications and analysis of factors that affect the accuracy of mobile merchant monitoring GPS applications on smartphones. After getting the results it is known that the accuracy of the coordinates on the GPS is not only determined by the internet network, the weather factors also determine the GPS in determining the exact coordinates.